Construction of Optimal Portfolio and Selection of Stock using Fuzzy Approach - Patni, Ity; Gupta, Nishu (International Journal of Engineering and Technology, 2018)
Stock selection methods and strategies have been the prominent area of research since long. Portfolio theory is a connotation how an intelligent bias free investor should make an optimal portfolio. The line of the work is first inclined towards construction of optimal portfolio using Sharpe-Single Index model, CAPM, Jensonâ€™s Measure, Treynor & Sharpe Ratio. These measures consider total risk i.e. systematic and unsystematic risk and suggests a rational investor in what proportion an investment can be made to a particular stock. Further, the purpose of the work is to combine the fuzzy approach for closer representation with reference to stock selection problem in a non-linear and uncertain environment. For demonstration, data set is taken from National Stock Exchange (NSE) for a period of 6 years (1st April, 2011 to 31st March, 2017). The proposed model will serve both ranking and assigning weight procedures to the selected stocks.Â Â